2017
DOI: 10.1177/2165079917705669
|View full text |Cite
|
Sign up to set email alerts
|

Situational Factors Associated With Burnout Among Emergency Department Nurses

Abstract: Emergency departments are high-stress environments for patients and clinicians. As part of the clinical team, nurses experience this stress daily and are subject to high levels of burnout, which has been shown to lead to hypertension, depression, and anxiety. Presence of these diseases may also contribute to burnout, creating a cycle of stress and illness. This prospective qualitative study used a phenomenological approach to better understand factors associated with burnout among emergency department nurses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 9 publications
2
42
0
4
Order By: Relevance
“…Despite the fact that the impact of working in an ED on the level of stress and burnout among nurses has now been established [54][55][56], less is known about its impact on job satisfaction. In the present study, it was found that the level of job satisfaction among the participants was moderate, which is consistent with another study [28].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the impact of working in an ED on the level of stress and burnout among nurses has now been established [54][55][56], less is known about its impact on job satisfaction. In the present study, it was found that the level of job satisfaction among the participants was moderate, which is consistent with another study [28].…”
Section: Discussionmentioning
confidence: 99%
“…Overcrowding of the ED as a result of prolonged ED LOS increases workload and predisposes ED staff to burnout (Schooley, Hikmet, Tarcan, & Yorgancioglu, ; Stefano et al, ). This leads to reduced staff numbers and a vicious cycle of even longer ED LOS resulting in even more overcrowding (Rathlev et al, ; Rozo, Olson, Thu, & Stutzman, ; Stefano et al, ). In Australia, the nationwide 4‐hour target for all ED patients (Sullivan et al, ) recognizes the importance of minimizing ED LOS.…”
Section: Introductionmentioning
confidence: 99%
“…51 Another study also reported its negative effects on the physical, emotional, interpersonal, and attitude-related aspects of behavior. 34 Obviously, burnout and its subsequent problems can reduce nurses' efficiency, job satisfaction, and motivation for quality care delivery. Strategies to enhance nurses' job satisfaction and productivity can encourage their involvement in decision-making, reduce their occupational stress, reducing their job burnout and improving their quality of work life.…”
Section: Discussionmentioning
confidence: 99%
“…5,9,30 Moreover, factors such as injustice, lack of rewards for nurses 5 , nursing staff shortage, heavy workload, and frequent night or rotational shifts with subsequent sleep problems can result in job dissatisfaction and burnout among nurses. 5,[33][34][35] Interpersonal factors: Nurses may experience job burnout due to interpersonal factors such as lack of social support, criticism by manager, inappropriate physiciannurse relationships, conflict with colleagues, and familywork conflict. 30,36 Intrapersonal factors: Intrapersonal factors behind job burnout include demographic factors such as gender, age, educational level, marital status, and work experience.…”
Section: The Findings Of the Theoretical Phasementioning
confidence: 99%